2006
DOI: 10.1007/s11325-006-0080-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency surgery of the tongue base in the treatment of snoring—a pilot study

Abstract: In a previously published study, a significant reduction of snoring was reported after treatment with radiofrequency surgery of the tongue base in patients suffering from obstructive sleep apnea syndrome. The aim of this study was to investigate the efficacy of radiofrequency surgery of the tongue base in the treatment of primary snoring. Twenty patients suffering from primary snoring (AHI < 10/h, body mass index < 32 kg/m(2)) and an isolated hypertrophic tongue base at clinical examination were enrolled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
(46 reference statements)
0
4
0
2
Order By: Relevance
“…MES operating at frequencies > 2.5-3 MHz) with other surgical and/or ablative modalities, based mostly on animal models 4,5,[24][25][26][27] and rarely on clinical design. [28][29][30] This preliminary study is the first to our knowledge attempting a histological and immunohistochemical comparison of LTI produced during incision of porcine skin by CO2-laser, MES, and MRS and its effects on wound healing. A study of similar design, comparing the same instruments, based solely on histological findings, has been conducted by Silverman et al (2007).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…MES operating at frequencies > 2.5-3 MHz) with other surgical and/or ablative modalities, based mostly on animal models 4,5,[24][25][26][27] and rarely on clinical design. [28][29][30] This preliminary study is the first to our knowledge attempting a histological and immunohistochemical comparison of LTI produced during incision of porcine skin by CO2-laser, MES, and MRS and its effects on wound healing. A study of similar design, comparing the same instruments, based solely on histological findings, has been conducted by Silverman et al (2007).…”
Section: Discussionmentioning
confidence: 94%
“…However, few studies have been conducted to compare the relatively recently introduced in clinical practice MRS (i.e. MES operating at frequencies > 2.5–3 MHz) with other surgical and/or ablative modalities, based mostly on animal models 4,5,24–27 and rarely on clinical design 28–30 …”
Section: Discussionmentioning
confidence: 99%
“…Welt et al identified a poor sustained improvement in snoring following single modality radiofrequency treatment in patients with isolated tongue base hypertrophy [32]. This highlights the importance of dynamic airway assessment prior to any intervention.…”
Section: Tongue Basementioning
confidence: 99%
“…This technique’s principal advantage relates to its minimal invasiveness, causing little pain, and the ability to perform under local anaesthetic in some institutions [32]. As with radiofrequency treatment to the soft palate, the disadvantages are associated with the recurrence in symptoms during long-term follow-up and the potential need for multiple treatments [26].…”
Section: Tongue Basementioning
confidence: 99%
“…(159,247) Ακόμη, πλήθος μελετών συγκρίνουν τις ιστικές επιδράσεις ΜΗΧ και laser CO 2 με εκείνες του συμβατικού μαχαιριδίου (103,158,232,234,238) ή και άλλων εργαλείων ιστικής διατομής, όπως τα διοδικά lasers, (179) τα lasers KTP (157) και Nd:YAG (143,146) ή το υπερηχητικό μαχαιρίδιο (105,226,237) Ωστόσο, λόγω της σχετικά πρόσφατης εισαγωγής της ΥΜΗΧ (που παράγει ηλεκτροχειρουργικό ρεύμα συχνότητας ανώτερης των 2.5-3MHz) στην καθημερινή κλινική πράξη μέχρι σήμερα έχουν διεξαχθεί λίγες μελέτες με σκοπό την σύγκρισή της με άλλα εργαλεία ιστικής διατομής, κυρίως βασιζόμενες σε ζωικά πειραματικά πρότυπα (153,155,156,(248)(249)(250) και σπανιότερα σε κλινικό σχεδιασμό. (12,161,166,240,(251)(252)(253) Η παράπλευρες φωτοθερμικές μεταβολές διαφοροποιούνται σημαντικά ανάλογα με την διάμετρο του σημείου εστίασης της φωτεινής δέσμης. (241) Η εφαρμογή πειραματικού ερευνητικού πρωτοκόλλου για την επίτευξη του σκοπού της μελέτης επιβάλλεται για λόγους κυρίως ηθικής και δεοντολογίας αλλά και για θέματα πρακτικής ευκολίας.…”
Section: κωδικοποίηση των παρασκευασμάτωνunclassified